Current Status and Prospects of Screening for Newborn Hereditary Metaboolic Disease - GU Xuefan; HAN Lianshu; YU Yongguo (罕见病研究, 2022)
Newborn screening is an effective measure for early detection and early treatment of rare genetic diseases. Among the three-level preventive measures to reduce birth defects, newborn screening has a significant preventive effect, and continues to develop with the advancement of new therapies and new technologies. Newborn screening is also relatively more reliable to obtain data on the prevalence of rare diseases. This article introduces the history and current status of neonatal screening for newborn hereditary metabolic disease in China, presents the disease spectrum and prevalence of 7 819 662 cases of neonatal screening by tandem mass spectrometry, and proposes 12 rare diseases as the primary targeting diseases for newborn screening by tandem mass spectrometry in China. At last, the article raises and discusses the issues of requirement for technology development and ethics of newborn screening.